METHODOLOGICAL IMAGE RESEARCHING BACKGROUND OF THE STATE BORDER GUARD SERVICE OF UKRAINE - Бобровський, Т.А. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2013)
The article deals with scientific results analysis of the image problem of the state structures within public administration, political science, psychology and law to seek methodological approaches and methods for image researching of the State Border Guard Service of Ukraine. It is concluded that communicative and managerial approaches and usage of comparative studies are needed to combine.